Mechanical spectroscopy of multiwalled carbon nanotube-filled polyurethane nanocomposites / Shahrul Azam Abdullah and Lars Frormann - Abdullah, Shahrul Azam; Frormann, Lars (Universiti Teknologi MARA, 2022)
Reinforced polyurethane composites provide possibility for tailoring material stiffness and combine the mechanical properties of fillers with behavior of matrix. This research work focuses on analyzing the mechanical behavior of polyurethanes filled with carbon nanotubes. Multi-walled carbon nanotube-filled polyurethane nanocomposites containing 7.8 to 30.5 vol%-MWNTs have been formulated by mixing and injection molding and their mechanical spectroscopy has been investigated. Tests including Dynamic Mechanical Analysis (DMA) and Thermogravimetric Analysis (TGA) were conducted at a frequency range of 1-50 Hz and the attributes were measured as a function of the intensity of the filler. With the concentration of the fillers, the storage modulus of nanocomposites increased, which also implies an increase in stiffness, inferring a good adherence between fillers and the matrix of polyurethane. The addition of more MWNTs to the nanocomposites broadened and lowered tan peak specifies that the polyurethane nanocomposite is more elastic as the fillers and the matrix are well adhered to. The reliance of the storage modulus is more pronounced in initial glassy region of the polymer. The presence of MWNTs has also improved the activation energy of the polymer. In addition, thermogravimetric analysis shows that the inclusion of MWMTs fillers enhances the thermal stability of the nanocomposites. This work has suggested that the incorporation of MWNTs into polyurethanes matrix can improved the mechanical properties well as their thermal stability.